PREVALENCE OF DEPRESSION AND ITS DETERMINANTS AMONG INDONESIAN DOMESTIC WORKERS IN MALAYSIA - PURBA, Ellys Juwita; SYED ABDULLAH, Syed Mohamad (Studia Universitatis Babeș-Bolyai Negotia, 2019)
Indonesian women migrant workers are a big population in most Asian countries. Past research indicates a large percent of Indonesian domestic workers being exposed to exploits, verbal and sexual abuse that further exposes them to various problems such as psychological, social, cognitive, behavioural, and physical challenges. Few subjects have thus far have been taken out on the prevalence of and associate factors with depression among Indonesian domestic workers in Malaysia. The objective is to know the prevalence of and the associated elements of depression among Indonesian domestic workers in Malaysia. This study engaged mix method. Quantitative information was accepted from 380 respondents by using Beck depression inventory (BDI-II), while qualitative data was collected from selected 32 respondents who have moderate depression (BDI-II) through interview. The questionnaire of total randomly 380 subjects were retrieved and 228 where participants who have depression symptom according to BDI-II. Three from five Indonesian domestic workers in Malaysia are having a depression symptom (60 percent). This study found that occupation, financial hardship, social support, and level education are the associate factors of depression among Indonesian domestic workers in Malaysia. Meanwhile, most of domestic workers who live with their employer have a moderate to severe depression. The awareness created through this study will enable proper government-to-government policy on domestic migrant workers matters, hence reducing the low rate and policy level intervention. It will as well contribute to the consistency of knowledge on depression of Indonesian domestic workers in a foreign country, especially the advocates and the social workers employed by the Indonesia embassies in all countries. JEL classification: J08, J15